PERAN DIET DASH DENGAN METODE PEER GROUP TERHADAP POLA MAKAN PENDERITA DIABETES MELLITUS - Nafolion Nur Rahmat; Kurniawan Erman Wicaksono; Sena Wahyu Purwanza (STIKES Garuda Putih, 2026)
Diabetes mellitus is a chronic health problem with an increasing prevalence, including in Kalibuntu Village, Probolinggo Regency. Unhealthy dietary patterns are a major factor that worsen the condition of patients, while the implementation of appropriate diets is often hindered by limited knowledge and lack of social support. This community service program aimed to improve the dietary patterns of diabetes patients through the application of the DASH diet (Dietary Approaches to Stop Hypertension) using a peer group approach. The method consisted of education and group-based mentoring carried out in three stages: preparation, implementation, and evaluation. Participants were diabetes patients with high blood glucose levels in Kalibuntu Village. Interventions included health education, small group discussions with facilitators, and the establishment of peer groups to share experiences and provide mutual support. Evaluation was conducted by comparing participants’ knowledge and skills before and after the intervention. The results showed a significant improvement in participants’ understanding of healthy eating patterns, ability to control food intake, and motivation to adhere to the DASH diet. Participants also demonstrated active engagement in discussions and commitment to adopting a healthy lifestyle. The peer group approach proved effective in strengthening social support, which positively influenced health behavior changes. Therefore, implementing the DASH diet through peer group methods can serve as a sustainable promotive and preventive strategy in diabetes management at the community level